La gallinita roja = The little red hen - Ottolenghi, Carol, 1959-; Holladay, Reggie (Columbus, OH : Brighter Child, an imprint of School Specialty Publishing, 2008)
A retelling of the familiar fairy tale in which the Little Red Hen, unable to get her friends to help her with her bread-making project, refuses to share the fruits of her labor.
Keywords: Animals -- Folklore; Fairy tales; Animales -- Folklore -- Literatura juvenil; Cuentos de hadas -- Literatura juvenil